Challenges and Opportunities for Technology and Language Learning in Sub-Saharan Africa - Nsyengula, Stephen; Haule , J, Emmanuely; Mhagama, Willy; Wang'uba Okello, Joel; Yassin, Anna (Journal of Classroom Action Research, 2025)
Sub-Saharan Africa has experienced a technological revolution in recent decades, with the rapid propagation of mobile devices and internet access influencing various aspects of life. This technological advancement has opened new frontiers for language learning in education, presenting both challenges and opportunities, particularly in the Mbeya region of Tanzania. This qualitative study explores the current state of technology-assisted language learning in Mbeya, identifying key obstacles and potential for growth. Through in-depth interviews and Focussed Group Discussions with educators, students, and policymakers, the research delves into the access and utilisation of technological resources within the language learning ecosystem. The findings of this study are significant, revealing disparities in connectivity, device availability, and digital literacy, particularly among marginalised communities, which limit their ability to fully leverage technology for language acquisition. However, the study also underscores the necessity of a comprehensive, multi-pronged strategy that includes investments in infrastructure, teacher training, and culturally relevant digital content. This strategy is urgent and crucial, aiming to inform stakeholders and contribute to developing equitable and sustainable technology-enhanced language learning strategies in Mbeya and beyond. Keywords:  Technology-assisted language learning; Teacher Training, Educational inequalities